Asymptomatic SARS Coronavirus 2 infection: Invisible yet invincible (2020)
While successful containment measures of COVID-19 in China and many European countries have led to flattened curves, case numbers are rising dramatically in other countries, with the emergence of a second wave expected. Asymptomatic individuals carrying SARS-CoV-2 are hidden drivers of the pandemic, and infectivity studies confirm the existence of transmission by asymptomatic individuals. The data addressed here show that characteristics of asymptomatic and presymptomatic infection are not identical. Younger age correlates strongly with asymptomatic and mild infections, and children as hidden drivers. The estimated proportion of asymptomatic infections ranges from 18% to 81%. The current perception of asymptomatic infections does not provide clear guidance for public-health measures. Asymptomatic infections will be a key contributor in COVID-19 spread. Asymptomatic cases should be reported in official COVID-19 statistics.